Gregory Baum on Nationalism and Ethics: The Case of Quebec - Seljak, David (Théologiques, 2021)
After moving to Quebec in 1986, Gregory Baum articulated an ethics of nationalism by examining the works of religious thinkers who adopted a critical appreciation of nations and nationalism. Baum argued that, while nationalism could promote chauvinism and even violence, it could also serve as a defense against colonialism and the imperialism of universalizing systems of governance. His sensitivity to the moral ambiguity of nationalism was inspired as much by his experience of nationalism in Germany, Ontario, and, especially, Quebec as by his Critical Theology. Baum’s analysis attempted to provide criteria for acceptable forms of nationalism. He believed that mainstream Quebec nationalism met these criteria. This paper attempts to connect Baum’s biography and social location with his theoretical work and argues that his ethics of nationalism is unthinkable without an understanding of his experience to Quebec.